The effect of the royal wedding on the UK stock market - Huy Pham; Vikash Ramiah; Hanh Le; Nisreen Moosa; Osama M. Al-Hares (Cogent Economics & Finance, 2022)
We assess the effect of the recent royal wedding of Prince Harry and Meghan Markle on various sectors of the UK stock market over the period between November 2017 and May 2018. For this purpose, the event study methodology is used to estimate abnormal returns and conduct several robustness tests such as the Corrado ranking test, the Chesney non-parametric conditional distribution approach, the Fama-French five-factor model, the market model, allowing for market integration, and the removal of firm-specific information. In addition, we use various ARCH-type models to capture changes in systematic risk. The results show that the effect of the royal wedding is limited to few sectors. We also find that a positive national and investor mood does not always boost sectoral stock returns. In addition, we observe that announcements related to the royal wedding led to changes in both short-term and long-term systematic risk.
Keywords: G1; G12; G14; 330; royal wedding; abnormal returns; event study; systematic risk